2007
DOI: 10.1007/s00441-007-0482-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperosmotic stress on cultured airway epithelial cells

Abstract: Inhalation of hyperosmotic solutions (salt, mannitol) has been used in the treatment of patients with cystic fibrosis or asthma, but the mechanism behind the effect of hyperosmotic solutions is unclear. The relation between osmolarity and permeability changes was examined in an airway cell line by the addition of NaCl, NaBr, LiCl, mannitol, or xylitol (295-700 mOsm). Transepithelial resistance was measured as an indicator of the tightness of the cultures. Cell-cell contacts and morphology were investigated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 35 publications
1
20
2
Order By: Relevance
“…Electrophysiology experiments cannot be done on the coral oral tissue owing to technical limitations, but structural similarities between coral and anemone oral tissues [42] suggest that results should be comparable, and if this was the case the higher resistance of the tissues of S. pistillata would be due to the paracellular junctions of the aboral tissue. In epithelia, permeability due to the paracellular pathway is known to increase under hyperosmotic conditions with non-electrolyte solutions by opening junctions [32,43]. In this study, we have observed that a hyperosmotic shock leads to a decrease in microcolony resistance, and thus an increase in tissue permeability.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Electrophysiology experiments cannot be done on the coral oral tissue owing to technical limitations, but structural similarities between coral and anemone oral tissues [42] suggest that results should be comparable, and if this was the case the higher resistance of the tissues of S. pistillata would be due to the paracellular junctions of the aboral tissue. In epithelia, permeability due to the paracellular pathway is known to increase under hyperosmotic conditions with non-electrolyte solutions by opening junctions [32,43]. In this study, we have observed that a hyperosmotic shock leads to a decrease in microcolony resistance, and thus an increase in tissue permeability.…”
mentioning
confidence: 56%
“…Since it was impossible to separate the oral tissue from the aboral tissue in S. pistillata, we measured the resistance of the oral tissue of the sea anemone A. viridis and obtained a value of 15 + 3 Ohm cm 2 . We then performed a hyperosmotic shock, which is usually used to determine if junctions are involved in the paracellular resistance of tissues [32]. When the hyperosmotic shock was performed in the hemi-chamber facing the tissues (apex) of a microcolony, the resistance decreased as a function of time (electronic supplementary material, figure S3).…”
mentioning
confidence: 99%
“…The presence of mannitol, which was the sole extra excipient in the powder formulations, could partly explain the increase in transfection efficiency. Hyperosmotic mannitol solution is known to be able to open up tight junctions between adjacent cells, therefore increasing the accessibility of DNA complexes to the cell surface [47,48] and the increase in transfection appeared in a mannitol dose dependent manner. However the mannitol in our powder formulations would have been present at a final concentration of 0.25% (w/v) and this may be too low to produce any prominent osmotic effect to the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, increasing the osmolarity from FW to 305mOsm L15 (48h recovery from 3mOsm) decreased claudin 28b fluorescence in control cultures significantly, which was in line with reduced TER values. In airway epithelial cells hyperosmotic exposure decreased claudin-4 in the tight junctions as well (Nilsson et al, 2007).…”
Section: Claudin 28b Tight Junction Fluorescence Correlates With Epitmentioning
confidence: 94%